Tuscan Spaces : Literary Constructions of Space - Ross, Silvia, 1967- (Book collections on Project MUSE., 2010)
In Tuscan Spaces, Silvia Ross focuses on constructions of Tuscany in twentieth-century Italian literature and juxtaposes them with English prose works by such authors as E.M. Forster and Frances Mayes to expose the complexity of literary representation centred on a single milieu.